Environmental and individual exposure to secondhand aerosol of electronic cigarettes in confined spaces: Results from the TackSHS Project†. (27th April 2021) - Amalia, Beladenta; Fu, Marcela; Tigova, Olena; Ballbè, Montse; Castellano, Yolanda; Semple, Sean; Clancy, Luke; Vardavas, Constantine; López, Maria J.; Cortés, Nuria; Pérez‐Ortuño, Raúl; Pascual, José A.; et al.
Abstract: Secondhand electronic cigarette (e‐cigarette) aerosol (SHA) might impair indoor air quality and expose bystanders. This study aims to investigate exposure to SHA in controlled conditions of enclosed settings simulating real‐world scenario. An experiment was performed in a car and in a room, in which SHA was generated during a 30‐minute ad libitum use of an e‐cigarette. The experiment was replicated on five consecutive days in each setting. We measured PM2.5, airborne nicotine concentrations, and biomarkers of exposure to SHA, such as nicotine metabolites, tobacco‐specific nitrosamines, propylene glycol, and glycerol in bystanders' saliva samples before, during, and after the exposure period. Self‐reported health symptoms related to exposure to SHA were also recorded. The results showed that the highest median PM2.5 concentration was recorded during the exposure period, being 21 µg/m 3 in the room setting and 16 µg/m 3 in the car setting—about twofold increase compared to the baseline. Most concentrations of the airborne nicotine and all biomarkers were below the limit of quantification in both settings. Bystanders in both settings experienced some short‐term irritation symptoms, expressed as dry throat, nose, eyes, and phlegm. In conclusion, short‐term use of an e‐cigarette in confined spaces increased indoor PM2.5 level and caused some irritation symptoms in bystanders.